2003
DOI: 10.1124/dmd.31.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Metabolism, and Excretion of Etoricoxib, a Potent and Selective Cyclooxygenase-2 Inhibitor, in Healthy Male Volunteers

Abstract: ABSTRACT:[ 14 C]Etoricoxib (100 Ci/dose) was administered to six healthy male subjects (i.v., 25 mg; p.o., 100 mg). Following the i.v. dose, the plasma clearance was 57 ml/min, and the harmonic mean half-life was 24.8 h. Etoricoxib accounted for the majority of the radioactivity (ϳ75%) present in plasma following both i.v. and p.o. doses. The oral dose, administered as a solution in polyethylene glycol-400, was well absorbed (absolute bioavailability of ϳ83%). Total recovery of radioactivity in the excreta was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 14 publications
0
45
0
2
Order By: Relevance
“…This reaction is mainly catalyzed by CYP3A (60%), but the rest is catalyzed equally between CYP2C9, CYP2C19, CYP2D6, and CYP1A2 [2,3]. Correspondingly, previous in vitro studies have indicated that miconazole is a nonselective inhibitor of several CYPs, namely CYP3A, 2C9, 2C19, 1A2, 2A6, and 2B6 [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction is mainly catalyzed by CYP3A (60%), but the rest is catalyzed equally between CYP2C9, CYP2C19, CYP2D6, and CYP1A2 [2,3]. Correspondingly, previous in vitro studies have indicated that miconazole is a nonselective inhibitor of several CYPs, namely CYP3A, 2C9, 2C19, 1A2, 2A6, and 2B6 [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Oral bioavailability of etoricoxib tablets is nearly 100% [1]. Despite its negligible first-pass metabolism, the elimination of etoricoxib is characterized by extensive metabolism, with less than 1% of an oral dose detected as unchanged drug in urine [2]. In vitro studies indicate that cytochrome P450 3A (CYP3A) is the most important enzyme catalyzing the primary metabolic pathway of etoricoxib (60%), with CYP2C9, CYP2D6, CYP1A2, and CYP2C19 each contributing about 10% [3].…”
Section: Introductionmentioning
confidence: 99%
“…For evaluation of pro-oxidant activity, the same treatment was performed in the presence of FeSO 4 (400 μM for plasma and 100 μM for aortic homogenate), to which (+)-ascorbic acid (10 mM for plasma and 500 μM for aortic homogenate) was added as a positive control for the Fenton reaction instead of the COX-2 inhibitors. Celecoxib (4 μM; Celecox® product information, Astellas Pharma Inc., Apr 2014), valdecoxib (1 μM: BEXTRA®, product information, Pfizer, July 2003) and etoricoxib (8 μM, Rodrigues et al, 2003) were also used for the experiments. The concentration of each COX-2 inhibitor was about the same as the maximum concentration when used clinically or in clinical trials, except for 200 μM rofecocxib.…”
Section: In Vitro Oxidation Assaymentioning
confidence: 99%
“…14 C]etoricoxib, and it can be estimated that about 75% of the dose (f m ϳ0.8) is cleared via P450-dependent 6Ј-methyl hydroxylation (Kassahun et al, 2001;Rodrigues et al, 2003). As in the case of rofecoxib, therefore, CYP2C9 plays a relatively minor role in the overall clearance of etoricoxib (f m ⅐ f m,CYP2C9(EM) Յ 0.2) ( Table 1).…”
Section: Rodriguesmentioning
confidence: 99%
“…In comparison to rofecoxib, the metabolic profile of etoricoxib is less complex and involves only P450-dependent 6Ј-methyl hydroxylation and 1Ј-N-oxidation as primary clearance pathways (Kassahun et al, 2001;Rodrigues et al, 2003). The 6Ј-methylhydroxy metabolite is major in human liver microsomes and is oxidized further to 6Ј-carboxy etoricoxib in the presence of cofactorfortified human liver cytosol.…”
Section: Rodriguesmentioning
confidence: 99%